Prinsip Dasar Muqaddimah Qanun Asasi Perspektif Pemikiran Hadratussyaikh KH. M. Hasyim Asyri - Husen, Fahmi; Hanifudin, Hanifudin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research discusses the fundamental principles of the Muqaddimah Qanun Asasi from the perspective of Hadratussyaikh KH. M. Hasyim Asy'ari, the founder of Nahdlatul Ulama (NU). This study employs a library research methodology with a descriptive-analytical approach, combining the analysis of various primary and secondary sources. The findings show that Hadratussyaikh emphasized the importance of unity among the ummah, the role of ulama as the chain of Ahlus Sunnah wal Jama'ah, mutual assistance, enjoining good and forbidding evil (amar ma'ruf nahi munkar), and prayers for the safety of the ummah, all while considering the socio-historical context, comprehensive methods of interpretation, and education. These principles not only serve as normative guidelines but also as a foundation for building a just, harmonious, and civilized society in accordance with moderate and inclusive Islamic values.